Health disparities among under-served populations implications for research, policy and praxis - Notaro, Sheri R. (Bingley, U.K. : Emerald, 2012)
Health Disparities Among Under-served Populations: Implications for Research, Policy and Praxis, focuses on a topic of national concern. Both disparities in health status and in health care reflect the continuing power of race, social class, and gender as forces that define the social determinants of health and the social, biological, and physical environments where groups live. Chapters focus on key issues that include substance abuse, psychological coping, trauma, infant mortality, HPV, environmental hazards, teen pregnancy, homeless youth, racism, discrimination, and cultural competence. The scholars who have contributed to this volume showcase their insight and keen analyses of these pressing issues through a variety of lenses, including but not limited to, sociology, economics, psychology, education, public health, history, urban studies, nursing, and environmental activism. This anthology critically examines the devastating impact of race, class, and gender on the health and health care of African Americans, Latinos and American Indians, with particular focus on children and adolescents.
Putting tribal nations first : historical trends, current needs, and future directions in substance use prevention for American Indian and Alaska native youths / Betty G. Brown, Julie A. Baldwin, Margaret L. Walsh -- Promotion of effective coping among adolescents of color / Jessie Kemmick Pintor, Carolyn Garcia, Ursula Reynoso -- Implementing trauma interventions in schools : addressing the immigrant and refugee experience / Olga Acosta Price ... [et al.] -- Health disparities in African American maternal and child health / Sheri R. Notaro -- Racial and global disparities in human papillomavirus infection and cervical cancer / Lauren D. Arnold, Vetta L. Sanders Thompson -- The buffalo lupus project : a community-based participatory research investigation of toxic waste exposure and lupus / Edith M. Williams ... [et al.] -- Teen pregnancy prevention among at-risk urban youth : improving parent-child connectedness / W. Douglas Evans ... [et al.] -- Overrepresentation and disparate outcomes : examining health disparities based on sexual orientation in the context of homeless youths / Maurice N. Gattis -- Beyond individual-level sexual risk behaviors : HIV/AIDS and racial health disparities / Portia E. Adams -- Sociohistorical privilege in higher education : implications for African American student psychological adjustment, resiliency, and success at predominately white institutions / Matthew J. Taylor ... [et al.] -- Can cultural competence have an impact on health disparities? / Brenda A. Battle -- Disparities in the prevalence of mental illness among black Americans / D. Lisa Cothran.
Includes index.
Keywords: Education -- Multicultural Education; Education -- Educational Policy & Reform -- General; Educational strategies & policy; Multicultural education; Minorities -- Medical care -- United States; Minorities -- Health and hygiene -- United States